Serum levels of glial fibrillary acidic protein and Nogo-A in children with autism spectrum disorders. (2nd October 2016) - Cetin, Ihsan; Tezdig, Ihsan; Tarakcioglu, Mahmut Cem; Kadak, Muhammed Tayyib; Demirel, Omer Faruk; Ozer, Omer Faruk
Abstract: Context: Improved biomarkers would facilitate the diagnosis and treatment of autism spectrum disorders (ASD). Objective: Our objective was to examine the levels of Nogo-A and glial fibrillary acidic protein (GFAP) in children with ASD. Materials and methods: Serum concentrations of GFAP and Nogo-A were determined by enzyme-linked immunosorbent assay. Results: In this preliminary study, we found that serum Nogo-A was not found significantly different between groups, while serum levels of GFAP were significantly lower in ASD than controls. Discussion and conclusions: It will be of great interest to determine other potential causes of elevated serum levels of GFAP, and whether this elevation has any phenotypic effect.